Chromosomes of the Asian water buffalo (Bubalus bubalis) - Rommelt Vasters, Claudia; Scheurmann, Elke; Jainudeen, Mohamed Razeen (Persatuan Doktor Veterinar Malaysia, 1978)
The chromosomes of the domestic water buffalo (Bubalus bubalis) have been studied using the C- and G- banding techniques. The diploid chromo- some numbers were 48 and 50 for the swamp and river (Murrah) type of water buffalo respectively. This difference in karyotype is due to a balanced autosomal 2/9 tandem fusion in the swamp buffalo